Phenological behavior of herbaceous and woody species in the highly threatened Ironstone Rupestrian Grasslands - Arruda, L. J.; Ranieri, B. D.; Cheib, A. L.; Morellato, L. P.C. [UNESP]; Fernandes, G. W.; Negreiros, D. (Elsevier, 2021)
The vegetation of ironstone rupestrian grasslands (canga) is of significant conservation concern due to the rapid encroachment of mining activity and urbanization on the remnants of this ecosystem. Ecological studies that address the phenological patterns of this vegetation are still scarce, although they are essential for its conservation, management, and restoration. The present study investigated the vegetative and reproductive phenology of 11 species (five herbaceous and six woody) in two distinct habitats of rupestrian grasslands (campo rupestre), canga couraçada and capão forest, both located in the Iron Quadrangle in Catas Altas, Minas Gerais, Southeast Brazil. Monthly phenological monitoring of populations of the selected species was performed over two consecutive years. Circular statistical analysis was used to evaluate the degree of synchrony and the significance of seasonality on deciduousness, leaf flushing, flowering, and fruiting of each species. Additionally, phenophases were compared between growth forms and between habitats of occurrence. Most herbaceous species were classified as evergreen and showed seasonal flowering in the rainy season, while woody species exhibited greater variability in leaf change pattern. There were significant differences in the phenological behavior between different growth forms for the four phenophases evaluated, while the comparison between habitats indicated differences in phenology only for deciduousness and flowering. Phenological differences between growth forms can be attributed to physiological strategies and seasonal water availability, the latter of which limits the phenology of most herbaceous species to the rainy season.
Keywords: Canga; Growth form; Seasonality; Synchrony; Threatened habitat